Pengaruh Terpaan Iklan di Televisi (Brand Awareness dan Brand Attitude) Vivo Smartphone dan Tingkat Kepercayaan tentang Informasi Vivo Smartphone dalam Peer Group Terhadap Keputusan Pembelian Produk Vivo Smartphone - Ayu Rafika Rosa; Sri Budi Lestari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Vivo Smartphone is one of smartphone brand with 99% advertisement placement on Indonesian television screens. The continually advertisements exposure can increase audience brand awareness and shape brand attitude towards Vivo Smartphone. However, with that advertisment frequency, Vivo Smartphone still cannot reach its target. Therefore, this research will discuss whether television advertising exposure (brand awareness and brand attitude) have influence on the purchase decision of Vivo Smartphone products. In addition, this reseacrch will also examined the influnce of the level of trust about Vivo Smartphone information among peer group toward purchase decision of Vivo Smartphone products. This research used Advertising Exposure Theory and Reasoned of Action Theory. The sample of this research were men or women aged 15-35 years domicile in Semarang who exposed to Vivo Smartphone advertisements on television and had discussed about Vivo Smartphone products with their peer group. The number of sample are 50 people with nonprobability sampling technique, with quota sampling type. Analysis of the data used was linear regression using the SPSS computered-program. The results of first hypothesis test showed that advertising exposure on television did not significantly influence Vivo Smartphone brand awareness with significance value of 0.941. Next the result of second hypothesis test, Vivo Smartphone brand awareness did not significantly influence brand attitude with significance value of 0.935. The third hypothesis test also showed that brand attitude did not significantly influence purchase decision of Vivo Smartphone product with significant value of 0.758. Meanwhile, the fourth hypothesis test showed that trust level of Vivo Smartphone information among peer group significantly influence purchase decision of Vivo Smartphone product with significance value of 0.042. The regression coefficience is 0.126 means that if there is an increase in the trust level of Vivo Smartphone information among peer group, the purchase decision of Vivo products will increase by 0.126. In addition, the trust levelof Vivo Smartphone information among peer group has influence of 8.3% on the purchase decision of Vivo Smartphone products.